2020
DOI: 10.1016/j.ejogrb.2020.10.023
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the Covid-19 pandemic on maternity services: A review of maternal and neonatal outcomes before, during and after the pandemic

Abstract: Highlights No negative impact on maternal or neonatal outcomes during the course of pandemic A decrease in preterm birth rate was found during the Covid-19 pandemic During the peak of the pandemic, there were less disclosures of domestic violence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
83
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 15 publications
8
83
1
2
Order By: Relevance
“…Of 3592 abstracts screened, 192 were relevant for full-text review and 40 met the inclusion criteria for systematic review ( figure 1 ). 4 , 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 A list of excluded studies with reasons for exclusion is provided in the appendix (p 6) . Reporting on resource use or service reconfiguration outcomes is summarised in the appendix (p 27) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 3592 abstracts screened, 192 were relevant for full-text review and 40 met the inclusion criteria for systematic review ( figure 1 ). 4 , 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 A list of excluded studies with reasons for exclusion is provided in the appendix (p 6) . Reporting on resource use or service reconfiguration outcomes is summarised in the appendix (p 27) .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 included studies, 31 for which comparable outcomes were also reported in at least one other study were included in the meta-analysis. 4 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 37 , 38 , 40 , 42 , 45 , 46 , 47 , 48 , 49 Table 1 shows the characteristics of the 40 included studies, all of which used a historical cohort design. 17 countries were represented, with substantial variation in pandemic mitigation measures among countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations